Communication Interaction Of Double Burden Batak Women In Patriarkhi Family In Gender Analysis In North Sumatra - Nursapia Harahap (CV. AFDIFAL MAJU BERKAH, 2022)
Study aim for knowing how interaction social family woman batak double burden in a patrilineal culture a gender analysis . Study this conducted with approach qualitative descriptive , collecting data with observation and interview to woman special double burden hobo woman scavenger , interaction social with children , husband and environment . This study is supported theory interactionalist Symbolic Herbert Blumer and the Hierarchy from Abraham Maslow . Research results show that woman working hobo _ as scavengers in system kinship patriarchy is bone back family Beside function reproduction , care child , serve husband and take care house stairs . Woman trying for Fulfill needs house stairs , education child children and social _ Attitude independent and work hard supported by existence expression culture